A Federated Approach in Training Acoustic Models - Dimitriadis, Dimitrios; Kumatani, Kenichi; Gmyr, Robert; Gaur, Yashesh; Eskimez, Sefik Emre (INTERSPEECH 2020, 2020)
In this paper, a novel platform for Acoustic Model training based on Federated Learning (FL) is described. This is the first attempt to introduce Federated Learning techniques in Speech Recognition (SR) tasks. Besides the novelty of the task, the paper describes an easily generalizable FL platform and presents the design decisions used for this task. Amongst the novel algorithms introduced is a hierarchical optimization scheme employing pairs of optimizers and an algorithm for gradient selection, leading to improvements in training time and SR performance. The experimental validation of the proposed system is based on the LibriSpeech task, presenting a speed-up of x1.5 and 6% WERR. The proposed Federated Learning system appears to outperform the golden standard of distributed training in both convergence speed and overall model performance. Further improvements have been experienced in internal tasks.